2020
DOI: 10.1101/2020.09.14.20194407
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Flushing of stagnant premise water systems after the COVID-19 shutdown can reduce infection risk by Legionella and Mycobacterium spp

Abstract: The unprecedented widespread closing of buildings due to the COVID-19 pandemic has allowed water to stagnate in premise plumbing systems, creating conditions that may facilitate the growth of opportunistic pathogens. In this study, we flushed and collected samples from showers in buildings that had been unoccupied for approximately two months and quantified Legionella pneumophila using a commercial cultivation-based assay. In addition, all bacteria, Legionella spp., L. pneumophila, L. pneumophila serogroup 1, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 47 publications
(77 reference statements)
2
24
0
Order By: Relevance
“…In comparison to free chlorine systems, chloramine systems are commonly reported to have lower L. pneumophila occurrence and concentrations, 15,6871 even in buildings with reduced occupancy. 44 Hypothesized reasons for lower L. pneumophila occurrence in chloramine systems include that monochloramine may better penetrate biofilms, 7275 may provide more persistent residuals in building plumbing, 76 and may more efficiently inactivate amoebal hosts or L. pneumophila within amoebae. 77,78 The few studies that examined L. pneumophila in distribution systems without a disinfectant residual generally reported low prevalence of L. pneumophila , 55,7982 though there have been reports of L. pneumophila occurrence in some building hot water systems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison to free chlorine systems, chloramine systems are commonly reported to have lower L. pneumophila occurrence and concentrations, 15,6871 even in buildings with reduced occupancy. 44 Hypothesized reasons for lower L. pneumophila occurrence in chloramine systems include that monochloramine may better penetrate biofilms, 7275 may provide more persistent residuals in building plumbing, 76 and may more efficiently inactivate amoebal hosts or L. pneumophila within amoebae. 77,78 The few studies that examined L. pneumophila in distribution systems without a disinfectant residual generally reported low prevalence of L. pneumophila , 55,7982 though there have been reports of L. pneumophila occurrence in some building hot water systems.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, other investigations of COVID-19 related building closures have reported that measurable disinfectant residuals were lacking in most samples. 44,48…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such water quality changes have been related to increased levels of OPs in premise plumbing systems [ 39 , 243 , 244 , 245 ]. In a field sampling study of main water distribution system, 120 water samples were taken throughout a drinking water distribution system.…”
Section: Influence Of Plumbing System Design Configuration and Opmentioning
confidence: 99%
“…Samples were collected within 1-2 weeks after students returned to on-campus residences, following a nearly stagnant and unused sewer system from March-August 2020. We hypothesized that flushing of stagnant water, lack of residual disinfectant, and idle plumbing may have contributed to changes in wastewater microbiome composition (47), with specific increases in the abundances of premise-plumbing associated pathogens such as Legionella pneumophila and Acinetobacter baumannii (48)(49)(50). For the first 5 days of the sampling period, when stagnant water was likely being flushed through the system, we found that there was an initial spike followed by a consistent decrease in the relative abundances of Legionella at 10 of the 15 sampling locations and of Acinetobacter at 7 of 15 sample locations (Figure S4).…”
Section: Temporal Patterns In the Taxonomic Composition Of The Prokar...mentioning
confidence: 99%